2018
DOI: 10.1111/pech.12285
|View full text |Cite
|
Sign up to set email alerts
|

Making and Keeping Promises: Regime Type and Power‐Sharing Pacts in Peace Agreements

Abstract: Power sharing is increasingly recognized as an important tool for creating sustainable peace in war‐torn societies. However, we have limited knowledge concerning why political, territorial, and military power‐sharing pacts are reached and implemented. This article addresses this gap by providing a global study examining the signing and implementation of power‐sharing pacts in intrastate armed conflicts. We focus on how the type of political regime can influence these choices and theorize about the strategic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…According to Mukherjee (2006), when civil wars end in a decisive military victory for either governments or insurgents, governments disproportionately gain support and legitimacy from the offer of a power‐sharing agreement, while insurgents lose support and legitimacy. Jarstad and Nilsson (2018:180) similarly find that regime type matters for the kind of power‐sharing agreements that are reached between former belligerents. Authoritarian regimes, they argue, are most likely to ‘implement pacts that do not pose a real threat to their authority, such as symbolic representation in a power‐sharing government’.…”
Section: To the Victor The Spoils? Power‐sharing As A Second‐best Oumentioning
confidence: 97%
“…According to Mukherjee (2006), when civil wars end in a decisive military victory for either governments or insurgents, governments disproportionately gain support and legitimacy from the offer of a power‐sharing agreement, while insurgents lose support and legitimacy. Jarstad and Nilsson (2018:180) similarly find that regime type matters for the kind of power‐sharing agreements that are reached between former belligerents. Authoritarian regimes, they argue, are most likely to ‘implement pacts that do not pose a real threat to their authority, such as symbolic representation in a power‐sharing government’.…”
Section: To the Victor The Spoils? Power‐sharing As A Second‐best Oumentioning
confidence: 97%
“…Regime type and the ideology of the government overseeing implementation matter. Based on the Implementation of Pacts (IMPACT) dataset (which builds on the Terms of Peace Agreements Dataset and information from the Uppsala Conflict Data Program), Jarstad and Nilsson (2018) analyze different challenges democracies and autocracies are likely to face when implementing and deciding on provisions in a PA, using a large-N analysis based on data on power-sharing provisions in 83 PA in 40 intrastate armed conflicts between 1989 and 2004. The literature reviewed by the authors indicates that the incentive structure for autocrats to maintain and implement agreements is weaker as they are not dependent on voters, while former warring parties will face higher local costs in democratic regimes for not upholding agreements.…”
Section: The Role Of Regime and Government Ideologymentioning
confidence: 99%
“…The literature reviewed by the authors indicates that the incentive structure for autocrats to maintain and implement agreements is weaker as they are not dependent on voters, while former warring parties will face higher local costs in democratic regimes for not upholding agreements. The authors found that territorial pacts are also more often signed in democracies than in autocratic states and that it is much likelier that the parties will reach a political or military pact in an autocratic than in a democratic system (Jarstad and Nilsson 2018). This is because "the incentive structure in authoritarian regimes suggests that the previous warring actors will use any means to stay in power" (Jarstad and Nilsson 2018, 180).…”
Section: The Role Of Regime and Government Ideologymentioning
confidence: 99%
“…In terms of studying the content of peace agreements, there is an increasing body of works which, for example, have explored how certain factors may influence specific stipulations such as political power-sharing and gender-sensitive provisions (Bell and O’Rourke, 2010; Jarstad and Nilsson, 2018; Svensson, 2009; True and Riveros-Morales, 2019). Only a few studies specifically examine why some peace agreements contain provisions that refer to civil society, or include civil society actors (e.g.…”
Section: Previous Researchmentioning
confidence: 99%